Para uma aborgadem institucionalista do voluntariado : o caso do voluntariado da Cruz Vermelha Portuguesa - Fernandes, Armando Jorge Teixeira (2012)
This article discusses volunteer action from an Institutionalist perspective. According to this approach, volunteer action is carried out by certain institutions through the creation of socio-economic contexts that stimulate cooperation (which is the essence of volunteer action) and in the context of emerging realities (crisis moments). To focus on these assertions, we look at two examples - the case of the Portuguese volunteer sector and the case of the Red Cross.